Obsessive‒compulsive symptoms and associated factors among people with schizophrenia attending services at referral hospitals in Eastern Ethiopia - Abdi Temesgen; Tilahun Abdeta; Daniel Alemu; Kemal Aliye; Abinet Zewudie; Dawit Abdi; Hirko Assefa; Rudwan Yasin (BMC Psychiatry)
Abstract Background Obsessive–compulsive symptoms are mental health conditions marked by the presence of obsessions and/or compulsions. Even though significant portion people with schizophrenia are reportedly affected by obsessive–compulsive symptoms, there is scarce of information related to this topic in Africa, and particularly in study area. Objective This study aimed to assess the magnitude and associated factors of obsessive‒compulsive symptoms among people with schizophrenia attending services at referral hospitals in Eastern Ethiopia from February 15 to March 15, 2024. Methods An institutional-based, cross-sectional study was conducted among adults with schizophrenia. Systematic sampling was used to select 422 study participants. The Yale-Brown Obsessive–Compulsive Scale was used to assess obsessive–compulsive symptoms. Data entry and analysis were performed by EpiData 4.6 and STATA 14, respectively. Bivariable and multivariable logistic regression were performed, and variables with p values < 0.05 were considered statistically significant. Results The proportion with obsessive‒compulsive symptoms in this study was 44.07% (95% CI, 39.33%-48.92%). After adjusting for possible confounders, duration of schizophrenia from 3–4 years (AOR = 3.41; 95% CI, 1.28–9.05), duration of schizophrenia 5 years and above (AOR = 6.08; 95% CI, 2.26–16.31), current use of alcohol (AOR = 2.12; 95% CI, 1.09–4.12), current use of khat (AOR = 6.09; 95% CI, 3.15–11.74), being a probable case of anxiety (AOR = 3.57; 95% CI, 1.95–6.53), being a probable case of depression (AOR = 4.56; 95% CI, 2.39–8.66), being on Risperidone (AOR = 5.08; 95% CI, 2.52–10.23) and being on Olanzapine (AOR = 5.95; 95% CI, 2.72–13.04) were significantly associated with obsessive‒compulsive symptoms. Conclusions and recommendation The prevalence of obsessive‒compulsive symptoms was relatively high. Timely detection and appropriate interventions are crucial and special consideration is better to be given for those with comorbid substance use, comorbid anxiety and depression, as well as those taking second-generation antipsychotics.